Age peculiarities for operated and non-operated adults with congenital heart disease - I. Lebid; N. Rudenko; V. Khanenova; I. Yemets (Ukrainian Journal of Cardiovascular Surgery, 2016)
The total number of patients with CHD who reach the age of 18 years, already currently consists of the operated patients, as well as those that do not require surgical correction. Evaluation of long-term follow up will improve the quality and term of their live. From 2011 to 2015, 2032 patients were examined, 52% of men and 48% of women, 18-88 years, (26.16±0.20), 1837 (90%) were younger than 40 years. significant advantage had Septal Defects (n=793; 39%) and Left Heart Lesions (n=488; 24%). The annual number of examined ACHD progressively increased (from 210 to 656). In the beginning of research there were younger patients (in 2011 – 24.62±0.75 y, and in 2014, 2015 – 28.70±0.72 and 29.28±0.69, p<0.05). There were pre-dominated patients after cardiac and surgery procedures, 80% had performed only one intervention. Patients with repeated interventions have a greater risk for future cardiac procedures.